2016
DOI: 10.1016/j.jphotobiol.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

The optical properties of mouse skin in the visible and near infrared spectral regions

Abstract: Visible and near-infrared radiation is now widely employed in health science and technology. Pre-clinical trials are still essential to allow appropriate translation of optical methods into clinical practice. Our results stress the importance of considering the mouse strain and gender when planning pre-clinical experiments that depend on light-skin interactions. Here, we evaluated the optical properties of depilated albino and pigmented mouse skin using reproducible methods to determine parameters that have wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 25 publications
2
81
0
1
Order By: Relevance
“…In this study, the thickness of the skin and muscle layers was measured by US. The optical attenuation was calculated using the optical properties reported in previous studies [31][32][33]. In addition, the limited bandwidth of the US data acquisition system dictates that the measurements at individual wavelengths are semiquantitative.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In this study, the thickness of the skin and muscle layers was measured by US. The optical attenuation was calculated using the optical properties reported in previous studies [31][32][33]. In addition, the limited bandwidth of the US data acquisition system dictates that the measurements at individual wavelengths are semiquantitative.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The choice of QC-1 dye with maximum absorption at 737 nm 62 within the optical window from 600 and to 1350 nm 63 with minimal light attenuation may have improved the detection of the signal. Furthermore, the ex vivo in situ nearinfrared fluorescence optical imaging and histopathologic studies confirmed the presence of intracamerally injected CF770/BSA in the right submandibular nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The approach was then repeated using our previously obtained mouse tumor images along with optical parameter values reported in the literature for mouse skin. , respectively [26]. Using these optical parameter values, and our calculated transform coefficients, we calculated a slope of 3.09 to use for the fluorescence depth estimates.…”
Section: In Vivo Tumor Depth Estimationmentioning
confidence: 99%